Microstructure and Corrosion Properties of Electrodeposited CoCrFeMnNi High Entropy Alloy Coatings - Yoosefan, Fateme; Ashrafi, Ali; Monir Vaghefi, Seyed Mahmoud (Frontiers in Materials, 2022)
This study investigated the effect of potential change on the microstructure and corrosion properties of CoCrFeMnNi HEA coatings synthesized by the electrochemical deposition method. The films were precipitated in an electrolyte based on a DMF-CH3CN organic system comprising Co, Cr, Fe, Mn, and Ni cations. GIXRD pattern in all samples showed a single face-centered-cubic structure. SEM-EDS results show that the coating morphology and the element's value in alloy composition vary at different coating potentials. Coatings were uniform and crack-free surfaces. The results of the wettability test showed all coatings were super-hydrophilic. All the alloys exhibited similar passivation and negative hysteresis processes in the CPP test. However, the 5 V sample exhibited a lower Epit value than the 6 V, and none of the samples were sensitive to pitting corrosion. The CPP test result showed that the corrosion current density of the 5V sample was 0.0525 μA/cm2, the minimum corrosion rate for the coated samples, and has improved the corrosion resistance of the substrate by about 44 times. The EIS test results showed the excellent performance of the coatings in enhancing the corrosion resistance compared to Cu substrate and similar alloy samples in a 3.5 wt. % NaCl solution, as the protection efficiency was about 90%. These High entropy alloy coatings are suitable for engineering applications in which higher corrosion protection is needed.